Hakikat Pendidik Dalam Pendidikan Islam - Jenal Abidin (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2022)
Abstract This article aims to determine the nature of educators in Islamic education. The method used in this paper is a library research approach that uses books and other literature as the main object. The type of research used is qualitative, namely research that produces information in the form of notes and descriptive data contained in the text under study. The results of this study state that the essence of educators is Allah SWT who teaches knowledge to humans and humans also have an obligation for him to transfer that knowledge to other humans for the benefit of humans including nature in it. Educators should develop and clean the souls of students so that they can get closer to Allah SWT, keep them away from evil, and keep them in their nature. Keywords: Educators, Duties, Roles and Responsibilities of Educators